Asset and debt deflation in the United States: How far can equity prices fall? - Philip Arestis; Elias Karakitsos (Levy Economics Institute of Bard College, 2003)
In an asset and debt deflation, the process of reducing debt by saving and curtailing spending takes a long time, say authors Philip Arestis and Elias Karakitsos. Current imbalances and poor prospects for spending in the private sector affect the balance sheets of the commercial banks. The downward spiral between the banks and the private sector induces a credit crunch that adversely affects the US economy, which is vulnerable to exogenous shocks and lacks the foundations for a new, long-lasting business cycle.
Keywords: 330; Börsenkurs; Wirtschaftslage; Konjunkturprognose; USA